Limited English proficient (LEP) immigrants in Ireland's District Court - Waterhouse, Kathryn (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2010)
The methodology used is exploratory, and Involves a triangulation of four research methods. The first method is ethnographic non-participant observation; over the course of seven months hundreds of cases were observed in a number of courts in and outside of Dublin. The choice of this methodology was based on the need to address the speculative and anecdotal nature of what is known about court interpreting. Complementing this method was a series of eighteen semi-structured interviews carried out with interpreters and solicitors/barristers; the style of interview supported the exploratory nature of the research. The third method involved a legal analysis of the right to an interpreter in Ireland using the case-law of relevant instruments, courts and bodies. Irish cases that ruled or commented on interpreting were also analysed to understand the extent to which interpreting issues have arisen and the language ideology of judges. The fourth and final method involved a review of existing reports, publications, studies and articles, as well as a qualitative content analysis of newspaper articles in two mainstream newspapers from 2000 to 2010. These sources, not previously exploited, enabled a broad picture to be painted of how interpreting was being portrayed in official reports, by the press, and in the reports of other interested bodies.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin